2013
DOI: 10.5194/hess-17-665-2013
|View full text |Cite
|
Sign up to set email alerts
|

Modelling monthly precipitation with circulation weather types for a dense network of stations over Iberia

Abstract: Abstract. Precipitation over the Iberian Peninsula (IP) is highly variable and shows large spatial contrasts between wet mountainous regions to the north, and dry regions in the inland plains and southern areas. In this work, we modelled the relationship between atmospheric circulation weather types (WTs) and monthly precipitation for the wet half of the year (October to May) using a 10 km grid derived from a highdensity dataset for the IP (3030 precipitation series, overall mean density one station each 200 k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 54 publications
(57 reference statements)
1
70
0
1
Order By: Relevance
“…A sensitivity test of Unclassified days on grid sizes and resolutions was performed in Demuzere et al (2009b), concluding that the number of these days would decrease with grid resolution. Other authors did not consider the Unclassified type due to the few cases in the particular study area and they decided to regroup Unclassified days among the retained classes (Trigo and DaCamara 2000;Cortesi et al 2013;El Kenawy et al 2014). Previous studies found a significant increase of portion of Unclassified days in summer and autumn when applying JC classification.…”
Section: Classification Of Wt: a Gridded Jc-implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…A sensitivity test of Unclassified days on grid sizes and resolutions was performed in Demuzere et al (2009b), concluding that the number of these days would decrease with grid resolution. Other authors did not consider the Unclassified type due to the few cases in the particular study area and they decided to regroup Unclassified days among the retained classes (Trigo and DaCamara 2000;Cortesi et al 2013;El Kenawy et al 2014). Previous studies found a significant increase of portion of Unclassified days in summer and autumn when applying JC classification.…”
Section: Classification Of Wt: a Gridded Jc-implementationmentioning
confidence: 99%
“…This classification, originally developed for the British Isles, has been one of the most prominent WT classification schemes applied in mid-high latitudes. An extensive number of studies that use the JC procedure can been found in the literature and they have mainly focused on Europe: Trigo and DaCamara (2000), Linderson (2001), Goodess and Jones (2002), Spellman (2000), Chen (2000), Grimalt et al (2012), Lorenzo et al (2008), Post et al (2002), Buishand and Brandsma (1997), Cortesi et al (2013), among others. Besides these areas, this scheme has been applied in other regions where it has been rarely used so far, such as USA (Wilby et al 1995), China (Liwei et al 2006), Taiwan (Lai 2010), Chile (Espinoza et al 2014), the Arabian Peninsula (El Kenawy et al 2014), or Russia (Spellman 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid anti-cyclonic (HYA) F < |Z| < 2F and Z < 0 point of view, a smaller number of weather types ensure a reasonable sample size for each type (Cortesi et al, 2013). To this end, the automated Lamb weather type method generates a daily circulation database for 10 basic groups (eight directional and two synoptic).…”
Section: Description (Acronym) Calculationmentioning
confidence: 99%
“…A relatively simple way to analyse the origin of rainfall in the PNOMP is to relate synoptic general atmospheric circulation patterns (ACPs) to local-scale precipitation (Goodess and Palutikof, 1998;Cortesi et al, 2013;Sapriza-Azuri et al, 2013, among others). This requires a method for classifying the ACPs into a discrete set of consistent ACP types.…”
Section: Elsevier_stoten_17069mentioning
confidence: 99%